Determination of Arbutin in Herbal Medicinal Products - N. P. Antonova (Ведомости Научного центра экспертизы средств медицинского применения, 2021)
Arbutin is the main active ingredient in many herbal medicinal products that have diuretic, antimicrobial, bactericidal, and antioxidant effects. Many of these products are mixtures of different herbal substances. Therefore, the approaches to quality control of HMPs can vary significantly. The aim of the study was to compare arbutin assay procedures used in quality control of arbutin-containing products. Materials and methods. Samples of the following HMPs were used in the study: monocomponent Bearberry Leaf and multicomponent Brusniver® (herbal mixture, powder). The test methods used were titrimetry, ultraviolet-visible spectrophotometry, and high-performance liquid chromatography (HPLC). Results. The authors compared five arbutin assay procedures described in the monographs and product files for arbutin-containing HMPs. Conclusions. It has been established that the analysed procedures cannot be used interchangeably as equivalent test methods; the limits for arbutin have to be established for each specific procedure. Iodometric titration is the most labour- and time-consuming method, and the determined titration endpoint is a subjective assessment. Spectrophotometric methods do not require the use of an arbutin reference standard, but they can give overestimated results as compared to the HPLC and titrimetry methods. HPLC methods are more selective, but they require the use of reference standards. The recommended test methods for HMP quality control are HPLC and visible spectrophotometry; the titrimetric method is recommended for replacement.